2020
DOI: 10.1186/s12954-020-00394-z
|View full text |Cite
|
Sign up to set email alerts
|

A national model of remote care for assessing and providing opioid agonist treatment during the COVID-19 pandemic: a report

Abstract: Background: Health services globally are struggling to manage the impact of COVID-19. The existing global disease burden related to opioid use is significant. Particularly challenging groups include older drug users who are more vulnerable to the effects of COVID-19. Increasing access to safe and effective opioid agonist treatment (OAT) and other harm reduction services during this pandemic is critical to reduce risk. In response to COVID-19, healthcare is increasingly being delivered by telephone and video co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 24 publications
0
56
0
1
Order By: Relevance
“…Many authors highlighted the important role of pharmacies in delivering HR interventions during a pandemictype situation if other services become unavailable [2, [43][44][45]. However, at such times, pharmacies may have reduced opening hours [31]. PWID who participated in the LUCID-B study reported finding the long queues for pharmacies at the start of lockdown very off-putting [23].…”
Section: Role Of Pharmaciesmentioning
confidence: 99%
“…Many authors highlighted the important role of pharmacies in delivering HR interventions during a pandemictype situation if other services become unavailable [2, [43][44][45]. However, at such times, pharmacies may have reduced opening hours [31]. PWID who participated in the LUCID-B study reported finding the long queues for pharmacies at the start of lockdown very off-putting [23].…”
Section: Role Of Pharmaciesmentioning
confidence: 99%
“…The adaptive effects of COVID-19 are potentially adverse – linked to risky substance use or reduced access to services – as well as productive for health – linked to how services and interventions and policies innovate in response. Drug treatment services globally have responded with a range of changes to the provision of OAT in an effort to reduce physical interactions since COVID-19 ( Basu et al, 2020 , Crowley and Delargy, 2020 , Dunlop et al, 2020 , EHRA, 2020 , EMCDDA, 2020b , Heimer et al, 2020 ). Historically, the system for OAT provision in many countries is based on supervised daily dosing of methadone and buprenorphine treatment, with the exception of buprenorphine treatment in the United States and France ( Dunlop, et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a second illustration of the potential opportunities of the current COVID-19 era, grey literature suggests a significant break-through in the deadlock of low threshold opioid agonist therapy schemes such as multiday prescriptions, in several countries including Morocco, Myanmar, Vietnam, Bangladesh, Iran, Nepal and India. ( UNoDC, WHO, HRI, INPUD, EUROPUD, 2020b ) , ( UNAIDS, n.d., 2000 ) , ( UNAIDS, 2020b ) , ( UNoDC, WHO, HRI, INPUD, EUROPUD, 2020a ) ( INPUD, 2020 )( Crowley & Delargy, 2020 )( WHO, 2009 )…”
Section: Multiday Prescriptions Of Opioid Agonist Therapy At Lastmentioning
confidence: 99%